Desorienterede kirketårne: Praktiske løsninger og arkitektoniske idealer i senmiddelalderens kirkebyggeri - Bertelsen, Thomas (Hikuin, 2006)
Alternatively placed church towers Practical solutions and architectural ideals in the late medieval churches By Thomas Bertelsen The main part of the Danish medieval church towers were built at the west gable of the church. However, in 47 cases the tower was alternatively placed (fig. 1, 2, note 2). Like most medieval church towers in Denmark these unusual examples are gothic. The majority were built in the Eastern part of Denmark, 17 alone on Zealand. The towers were alternatively placed due to a number of reasons. The landscape might have prevented a west tower or the tower could be erected above a chapel, porch or sacristy thus representing an economic solution (fig. 1, 3). However, practical reasons do not explain all alternatively placed towers. For instance, the tower of Drøsselbjerg church on Zealand is built in front of the south portal of the church, thus the tower is used as a porch (fig. 6). In this case the surroundings do not prevent a west tower and the many extensions of the church indicate that financial matters were not an issue. The line between practical solutions and architectural ideals in medieval buildings is not clear. However, some of the alternatively placed towers must be products of architectural considerations. Perhaps symbolism also played a role but as the alternatively places towers typically were raised above porches – a part of the church with no obvious liturgical purpose – symbolic reasons do no seem important.